New roles of civil society in achieving health security in algeria - benabbas, Saber; fellak, Noureddine (The journal of Teacher Researcher of Legal and political Studies, 2025)
This study aims to analyze the relationship between civil society organizations and health security by highlighting the new roles played by civil society in this context, in order to govern health policies and address all internal and external threats to health security, based on the mechanisms of volunteering and disseminating health culture, given their importance in enhancing health security in light of the spread of global epidemics. This study concluded that the contribution of civil society organizations to achieving health security in Algeria, despite its maturity, is still limited, as a result of a set of challenges related to the government’s management of the health system in Algeria. There are organizational and financial challenges associated with civil society organizations. Activating the role of civil society organizations in this field requires strengthening the logic of independence from the state and fostering a spirit of initiative in providing awareness and sensitization programs to confront potential epidemics.